2022
DOI: 10.1002/wlb3.01034
|View full text |Cite
|
Sign up to set email alerts
|

Antler detection from the sky: deer sex ratio monitoring using drone‐mounted thermal infrared sensors

Abstract: Sex differences in large mammals with sexual dimorphism are important ecological and evolutionary issues and key factors for wildlife management. To examine the potential use of drone (unmanned aerial vehicle; UAV) observation using thermal infrared images for sex ratio monitoring of deer, we conducted UAV surveys at night in a sparse forest located on the distribution periphery of sika deer Cervus nippon and wild boar Sus scrofa local populations during summer and winter. Of the 163 thermal infrared images of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Surveys using both sensors from dawn to early morning will also be effective for research on a single species, because mammals and other objects can be distinguished using RGB images (Figure 3e). This methodology will be effective for identifying the sex of sika deer, because we can combine the merits of RGB observation, which can recognize antler shapes and body colors (Liang et al, 2020), and thermal infrared observation, which can detect animals and velvet antlers (Ito et al, 2022). For more effective species detection and identification, image analysis using machine learning also has potential (Corcoran et al, 2021; Hollings et al, 2018; Seymour et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Surveys using both sensors from dawn to early morning will also be effective for research on a single species, because mammals and other objects can be distinguished using RGB images (Figure 3e). This methodology will be effective for identifying the sex of sika deer, because we can combine the merits of RGB observation, which can recognize antler shapes and body colors (Liang et al, 2020), and thermal infrared observation, which can detect animals and velvet antlers (Ito et al, 2022). For more effective species detection and identification, image analysis using machine learning also has potential (Corcoran et al, 2021; Hollings et al, 2018; Seymour et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Large mammal detection using thermal infrared sensors is effective (Figure 2), but the RGB sensor was virtually useless at night. Species identification using only thermal infrared images is possible between bears and ungulates if the animals are standing or moving (Figure 4) but difficult if the animals are sitting, which conceals their characteristic movements as previously shown with sika deer and wild boars (Ito et al, 2022). Identification using thermal infrared sensors alone is also not easy to distinguish between sika deer and Japanese serows, unless their shapes and movements can be observed closely.…”
Section: Identification Of Sika Deer and Japanese Serowmentioning
confidence: 94%
See 2 more Smart Citations
“…They found that other methodological challenges included the regulations limiting UAV use and weather conditions. Another recent study also tested antler detection with drone mounted TIR cameras, successfully identifying antlered deer at night during the antler growth period (Ito et al 2022).…”
Section: Introductionmentioning
confidence: 99%